2019
DOI: 10.1152/ajpcell.00059.2018
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of TMEM16A regulation: role of CaMKII and PP1/PP2A

Abstract: This study explored the mechanism by which Ca2+-activated Cl− channels (CaCCs) encoded by the Tmem16a gene are regulated by calmodulin-dependent protein kinase II (CaMKII) and protein phosphatases 1 (PP1) and 2A (PP2A). Ca2+-activated Cl− currents ( IClCa) were recorded from HEK-293 cells expressing mouse TMEM16A. IClCa were evoked using a pipette solution in which free Ca2+ concentration was clamped to 500 nM, in the presence (5 mM) or absence of ATP. With 5 mM ATP, IClCa decayed to <50% of the initial cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…Phospho-serine binding protein 14-3-3 directly interacts with ANO1 and also stabilizes ANO1 on cell surface by unknown mechanism, both in heterologous models and in glioblastoma U251 cells (Lee et al, 2016b). Cell surface expression of ANO1 is also promoted by Ca 2+/ Calmodulin-dependent protein kinase II (CaMKII) in heterologous models and in glioblastoma U251 cells (Sim et al, 2020), potentially (but not proven) through phosphorylation of ANO1 by CAMKII (Ayon et al, 2019). In contrast, β-COP, a subunit of Coat Protein Complex I (COPI), directly interacts with ANO1 and reduces its surface expression by promoting the retrograde transport, which was also shown at the endogenous levels of ANO1 and β-COP in U251 cells (Lee et al, 2016a).…”
Section: Regulation Of Ano1 Expressionmentioning
confidence: 99%
“…Phospho-serine binding protein 14-3-3 directly interacts with ANO1 and also stabilizes ANO1 on cell surface by unknown mechanism, both in heterologous models and in glioblastoma U251 cells (Lee et al, 2016b). Cell surface expression of ANO1 is also promoted by Ca 2+/ Calmodulin-dependent protein kinase II (CaMKII) in heterologous models and in glioblastoma U251 cells (Sim et al, 2020), potentially (but not proven) through phosphorylation of ANO1 by CAMKII (Ayon et al, 2019). In contrast, β-COP, a subunit of Coat Protein Complex I (COPI), directly interacts with ANO1 and reduces its surface expression by promoting the retrograde transport, which was also shown at the endogenous levels of ANO1 and β-COP in U251 cells (Lee et al, 2016a).…”
Section: Regulation Of Ano1 Expressionmentioning
confidence: 99%
“…Ayon et al 177 to support channel activity. 161 The rundown of ANO1 was partially attenuated by inhibiting CaMKII with KN-93 or the peptide inhibitor ARIP.…”
Section: Regulation Of Ano1 By Camkii-mediated Phosphorylationmentioning
confidence: 98%
“…4B). 54-56, 59, 84 Additionally, Ayon et al 177 carried out sitedirected mutagenesis to identify one or several potential sites for CaMKII phosphorylation. Of four sites bearing the consensus CaMKII sequence RxxS/T, only the S528A (identical to S525 in Lin et al 176 and corresponding to S471 in mouse ANO1ac; see Fig.…”
Section: Regulation Of Ano1 By Camkii-mediated Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…While direct a CAM-regulation of TMEM16A is discussed controversially, several studies demonstrate that CAM-dependent kinase II (CAMKII) regulates CaCC/TMEM16A. However, CAMKII was found to activate [ 8 , 9 , 10 , 11 , 12 ] and to inhibit [ 13 , 14 , 15 , 16 , 17 ] CaCC and TMEM16A, respectively. Greenwood and Leblanc found a cell-type-dependent activation/inhibition of CaCC by CAMKII [ 18 ], while Ko et al found differential regulation of TMEM16A by CAMKII, depending on the splice variant [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%